Behaviour of alkali activated concrete under marine conditions. Issue 1 (June 2020) - Saravanakumar, P; Kalaivani, P
Abstract: This study aims to investigate the mechanical and durability behavior of flyash and slag based alkali activated concrete mixes under marine conditions. To fulfil the aim of this study, various tests such as Compressive Strength test, Sorptivity test, Half Cell Potential test and Alkalinity tests were done on both flyash and slag based alkali activated concrete. The experimental results showed that the alkali activated concrete attains its strength at earlier stages when compared to control concrete and it also has low sorptivity value which influences much indurability under marine conditions. Though it was cured in acidic environment for four weeks the alkali activated concrete samples showed only intermediate risk of corrosion.